The Struggle for Pekař´s Chair: Václav Chaloupecký, František Hrubý, and the Generational Shift in ‘Czechoslovak’ Academic Historiography during the First Republic - Ducháček, Milan (Dějiny – teorie – kritika, 2014)
The generational, conceptual, and methodological transformation of the Czech (and Czechoslovak) historiography has traditionally been linked to the 1st Congress of Czechoslovak Historians which took place in 1937. The aim of this contribution is to examine this supposition and describe the circumstances which led to Václav Chaloupecký succeeding Pekař in the Prague chair of Czechoslovak history. In the background of the text, the author also questions the stereotype of ‘Czechoslovakism’ as a key concept of Czechoslovak interwar historiography, examines the (dis)continuity of ‘Goll’s school’, and investigates the rise of Marxist historiography in the Czech environment. In doing so, the author aims at creating a framework of interpretation based on a broader context than the hitherto prevailing focus on Prague, its academia and its academics tends to offer. Given the wide scope, however, the goal of the text is not to meticulously map the changes and shifts in Czechoslovak historiography of the period in question. Rather, the intention is to present a partial point of view, one intended as a possible prolegomenon to the range of issues outlined above.